Category of the sacred in religion (Journal of Philosophy Culture and Political Science, 2018)
The article analyzes the category of the sacred in the context of modern phenomenology of religion. Based on the widely ubiquitous in religion – concept of the sacred, the author tries to show its versatility and applicability for the interpretation of non-Christian religions and beliefs. Being an inherent part of religious tradition and culture of mankind, the sacred sets essential and valuable dimensions of human life and society benchmarks. Sacred invisible thread ties together the spiritual and the sacred beginning of man and feeds the roots. Alienation from the sacred, its loss leads to the dehumanization of social existence and identity fading spirituality. Modern theological-religious studies concepts of the sacred, revealing the essence of the concept, helping humanity to re-look into the origins of their spirituality and to revise the value system.Key words: religion, religious phenomena, sacred, profane, hierophany, sacralization.